The Effect of Abnormal Regional Homogeneity and Spontaneous Low-Frequency Brain Activity on Lower Cognitive Ability: A Cross-Sectional Study on Postoperative Children With Tetralogy of Fallot - Ma, Siyu; Hu, Yuanli; Liu, Yuting; Pu, Yiwei; Zuo, Pengcheng; Hu, Qinghui; Yang, Zhaocong; Chen, Feng; Xie, Zongyun; Cun, Yueshuang; Liu, Xiaoxu; Yang, Ming; et al. (Frontiers in Neuroscience, 2022)
Despite intracardiac malformation correction, children with Tetralogy of Fallot (TOF) may still suffer from brain injury. This cross-sectional study was primarily designed to determine the relationship between blood oxygenation level-dependent (BOLD) signal changes after surgery and cognition in school-aged children with TOF. To evaluate the differences between TOF children (n=9) and healthy children (n=9), resting-state functional magnetic resonance imaging (rs-fMRI) and the Wechsler Intelligence Scale for Children–Chinese revised edition (WISC-CR) were conducted in this study. The results showed that TOF children had a lower full-scale intelligence quotient (FSIQ, 95.444±5.354, p=0.022) and verbal intelligence quotient (VIQ, 92.444±4.708, p=0.003) than healthy children (FSIQ =118.500±4.330；VIQ=124.250±4.404), that significant differences in regional homogeneity (ReHo) and amplitude of low-frequency fluctuation (ALFF) were exsited between the two groups. Besides, VIQ had significantly positive correlations with the decreased ALFF value of the middle inferior occipital gyrus (MIOG, beta=0.908, p=0.012) after fully adjusting for all covariates. In addition, elevated ReHo values of the left and right precuneus were positively related to ALFF in the MIOG. This study revealed that brain injury substantially influences neural activity and cognition in postoperative TOF children, providing direct evidence of an association between BOLD signal changes and the VIQ and prompting further attention to language development in TOF children.